2022
DOI: 10.1021/jacs.2c02612
|View full text |Cite
|
Sign up to set email alerts
|

A Photo-responsive Transmembrane Anion Transporter Relay

Abstract: Ion transport across lipid membranes in biology is controlled by stimuli-responsive membrane channels and molecular machine ion pumps such as ATPases. Here, we report a synthetic molecular machine-like ion transport relay, in which transporters on opposite sides of a lipid bilayer membrane facilitate transport by passing ions between them. By incorporating a photo-responsive telescopic arm into the relay design, this process is reversibly controlled in response to irradiation with blue and green light. Transpo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 49 publications
(59 citation statements)
references
References 48 publications
2
40
0
Order By: Relevance
“…However, in these photo-switchable systems the OFF isomers typically have some background transport activity because they can inevitably bind anions to some extent. Azobenzene switching has also been used to regulate transport via a relay mechanism 22 and to control a membrane-spanning [2]rotaxane. 23 Irreversible redox modulation of anion binding affinity and therefore transport activity has also been reported for chalcogen bonding anionophores.…”
Section: Introductionmentioning
confidence: 99%
“…However, in these photo-switchable systems the OFF isomers typically have some background transport activity because they can inevitably bind anions to some extent. Azobenzene switching has also been used to regulate transport via a relay mechanism 22 and to control a membrane-spanning [2]rotaxane. 23 Irreversible redox modulation of anion binding affinity and therefore transport activity has also been reported for chalcogen bonding anionophores.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, highly selective methods, including stimuli-responsive protransporters, have been developed by several research groups including us to achieve control over the locus of action of the anionophores. 61,79,85,[87][88][89][90][91][92][93][94][95][96][97][98][99][100] Taken together, synthetic ion transport systems undoubtedly possess immense potential to be used as therapeutic agents in curing life-threatening diseases like cystic fibrosis and cancer. This field has grown rapidly, and new systems with improved efficiencies have recently been reported.…”
Section: Manzoor Ahmadmentioning
confidence: 99%
“…Langton and co-workers demonstrated that an artificial ion transporter on the opposite side of a lipid bilayer can serve as a molecular machine-like ion transport relay ( Figure 9 ) [ 136 ]. The transporter incorporates a photo-responsive stretchable arm that can be reversibly controlled in response to exposure to blue and green light.…”
Section: From Recent Examplesmentioning
confidence: 99%
“… Artificial ion transporter on the opposite side of a lipid bilayer can serve as a molecular machine-like ion transport relay using a photo-responsive stretchable arm. Reproduced under terms of the CC-BY license [ 136 ]. …”
Section: Figurementioning
confidence: 99%